Fra2 Overexpression in Mice Leads to Non-allergic Asthma Development in an IL-13 Dependent Manner - Gungl, Anna; Biasin, Valentina; Wilhelm, Jochen; Olschewski, Andrea; Kwapiszewska, Grazyna; Marsh, Leigh M. (Frontiers in Immunology, 2018)
Background: Asthma is a complex chronic inflammatory disease characterised by airway inflammation, remodelling and hyperresponsiveness (AHR). Members of the AP-1 transcription factor family play important roles in the activation of the immune system and the control of cellular responses; however, their role in the development of asthma has not been well studied. We aimed to investigate the role of the lesser known AP-1 family member, Fra2 in experimental asthma. Methods: Phenotypic characterisation and gene expression profiling was performed on Fra2 (TG) overexpressing and wild-type mice. The efficacy of therapeutic interventions in regulating the Fra2 phenotype was determined. Results: Transcriptional profiling of TG mice revealed a high abundance of regulated genes associated with airway remodelling, inflammation and mucus production. A concomitant increase in peribronchial collagen deposition, smooth muscle thickening and mucus production was observed. TG mice possessed increased inflammatory infiltration in the lung, predominantly consisting of eosinophils and T-cells and elevated expression of Th2 cytokines and eotaxin. Furthermore, TG mice possessed severe AHR in response to increasing doses of methacholine. Glucocorticoid treatment led to a partial improvement of the asthma phenotype, whereas blockade of IL-13 via neutralising antibodies ameliorated AHR and mucus production, but had no effect on collagen deposition. Conclusion: We could describe a novel model for non-allergic asthma that does not require the use of exogenous allergen application, which mimics several key features of the disease, such as airway inflammation, remodelling and hyperresponsiveness. Fra2 may represent a key molecule coordinating multiple aspects of asthma pathogenesis.